From Rio to Rio+20: Twenty years of participatory, long term oriented and monitored local planning? (2015)
This paper provides the first comprehensive review of peer-reviewed journal articles on Local Agenda 21 processes worldwide between 1992 (Rio Summit) and 2012 (Rio+20 Summit). An in-depth analysis is carried out on 90 articles selected from an initial sample of 420, in order to determine their profile in terms of time, geography, authors' field and methodological approach, and analyze their content to: (1) proxy the gap between the ideal Local Agenda 21 model and real-world Local Agenda 21 practices in terms of participation, and long-term orientation and monitoring; and (2) identify the causes of this gap and ways to overcome it. Our findings show that real-world Local Agenda 21 practices are far from fitting the ideal Local Agenda 21 model.